Neuzugang von äthiopischen Handschriften an die Staatsbibliothek zu Berlin, Preußischer Kulturbesitz - Six, Veronika (Aethiopica, 2007)
As already practiced before Aethiopica has become the medium for the description of newly acquired Ethiopian manuscripts. The Oriental section of the Berlin State Library has received two MSS: one containing praises for the Virgin and the other one, a Mäzmurä Dawit, decorated with several miniatures.